Step-by-step explanation:
[(-3 × 2 × (-4)] ÷ [-6 × 12]
[3 × 2 × -4] ÷ [-6 × 12]
[6 × -4]/[-6 × 12]
-4/(-1 × 12]
-4/-12
⅓
Option A is wrong
Option B is wrong -9/-18 = ½ not ⅓
Option C is correct = -24/-72 = ⅓
Option D is wrong = 9/-18 = -½ not ⅓
Step-by-step explanation:
- (a+2b+30)-(40+36-5a)
- a+2b+30-40-36+5a
- 6a+2b-46
hope it helps.
Answer:
Bye
Step-by-step explanation:
Figure it out yourself
Add 12 to both sides to get
5m= 50
divide by 5 to get
M=10
2(4-3x) is the answer to X2+(-x)+(-3x2)+(-5x)+12